Role of „Article 356‟ in History of Kerala Politics – A Reappraisal - Asha Rajan
History of democratic India is eventful with facts, where Article 356 is misused and wrongful advantages of power have been made. In simple terms this Article deals with the rules which allow the central government to dissolve the State Governments if it can be established that there is total anarchy in the State concerned. Anguished over the alleged killing of its workers recently in Kerala, the Rashtriya Swayamsewak Sangh (RSS) and its associates support calls for President's Rule in the State due to „deteriorating law and order situation‟. Article 356 has always been the focal point of a wider debate of the federal structure of government in Indian polity. The Sarkaria Commission Report on Centre-State Relations (1983) had recommended that Article 356 must be used "very sparingly, in extreme cases, as a measure of last resort, when all the other alternatives fail to prevent or rectify a breakdown of constitutional machinery in the state". Dr. Ambedkar also said that it would be like a "dead letter" (i.e. would be used rarely). But the practice was limited only after the Supreme Court established strict guidelines for imposing the President's Rule in its ruling on the S. R. Bommai vs. Union of India case in 1994. This landmark judgment helped curtail the widespread misuse of Article 356. Reviewing the dissolution of the first government in modern Kerala, attempt is made in this paper to establish that the dissolution of the first democratically elected government of Kerala in 1959 could have been challenged successfully in the court. Had it been so the history of Kerala would have been different.